First recorded outbreak of yellow fever in Kenya, 1992-1993. I. Epidemiologic investigations. - Sanders, E; Marfin, A; Tukei, P; Kuria, G; Ademba, G; Agata, N; Ouma, J; Cropp, C; Karabatsos, N; Reiter, P; Moore, P; Gubler, D (1998)
Outbreaks of yellow fever (YF) have never been recorded in Kenya. However, in September 1992, cases of hemorrhagic fever (HF) were reported in the Kerio Valley to the Kenya Ministry of Health. Early in 1993, the disease was confirmed as YF and a mass vaccination campaign was initiated. Cases of suspected YF were identified through medical record review and hospital-based disease surveillance by using a clinical case definition. Case-patients were confirmed serologically and virologically. We documented 55 persons with HF from three districts of the Rift Valley Province in the period of September 10, 1992 through March 11, 1993 (attack rate = 27.4/100,000 population). Twenty-six (47%) of the 55 persons had serologic evidence of recent YF infection, and three of these persons were also confirmed by YF virus isolation. No serum was available from the other 29 HF cases. In addition, YF virus was isolated from a person from the epidemic area who had a nonspecific febrile illness but did not meet the case definition. Five patients with confirmed cases of YF died, a case-fatality rate of 19%. Women with confirmed cases of YF were 10.9 times more likely to die than men (P = 0.010, by Fisher's exact test). Of the 26 patients with serologic or virologic evidence of YF, and for whom definite age was known, 21 (81%) were between 10 and 39 years of age, and 19 (73%) were males. All patients with confirmed YF infection lived in rural areas. There was only one instance of multiple cases within a single family, and this was associated with bush-clearing activity. This was the first documented outbreak of YF in Kenya, a classic example of a sylvatic transmission cycle. Surveillance in rural and urban areas outside the vaccination area should be intensified.